Hubungan Kualitas Pelayanan dengan Kepuasan Pasien di Puskesmas Cawas II - Riska Meilinawati; Siti Fatmawati (LPPM Universitas Proklamasi 45, 2023)
Service quality is a form assessment fom service users on what is received after receiving service from an agency. While patient satisfaction is a feeling of pleasure, sadness or disappointmen that ariss from service users after receiving service. Along with the increasing demand of service quality from the community, to create patient satisfaction, the service function will be improved. The achievement of SPM in Cawas II Community Health Centers in 2020 is 71,48% and in 2021 it is 84,06%. To know and identify the relationship between service quality and patient satisfaction at Cawas II Public Health Center. The study used quantitative methods with a cross sectional approach. Sampling using Quota Sampling technique, with a sample of 91 respondents. The results of the bivariate test prove that service quality is related to patient satisfaction, namely p value 0,00 and α 0,05 where p<α is said to have a relationship. The correlation value of 0,757 belongs to the category of “Strong Relationship”. There is a relationship between service quality and patien satisfaction at the Cawas II Public Health Center.